Isimujamii : nadharia na muktadha wa Kiswahili - Mekacha, Rugatiri D. K. (Dar es Salaam : Taasisi za Taaluma za Kiswahili, Chuo Kikuu cha Dar es Salaam, 2011)
A guide to sociolinguistics of the Swahili language.
Includes bibliographical references (p. 227-236).
In Swahili.
Keywords: Sociolinguistics -- Africa, East; Swahili language